2013
DOI: 10.4103/0019-5049.115621
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Truview EVO2 laryngoscope in the airway management of elective surgical patients: A comparison with the Macintosh laryngoscope

Abstract: Background:The Truview EVO2(C) laryngoscope (TL) is a recently introduced optical device designed to provide an unmagnified anterior image of the glottic opening and allow indirect laryngoscopy.Aim:This study is designed to determine whether the TL is a better alternative to the Macintosh laryngoscope (ML) for routine endotracheal intubations in patients with usual airway characteristics.Methods:We compared the Truview EVO2(C) and MLs in 140 elective surgical patients requiring general anaesthesia and intubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
(25 reference statements)
6
10
0
Order By: Relevance
“…While in Macintosh group, no patients had IDS score 1 while 37, 8 and 51 patients had IDS score 2, 3 and 4 respectively. 9,13,16 Thus, the result in our study was comparable to the above study. Table 5 shows subjective assessment of intubation in both the groups on the basis of Intubation Difficulty Score.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While in Macintosh group, no patients had IDS score 1 while 37, 8 and 51 patients had IDS score 2, 3 and 4 respectively. 9,13,16 Thus, the result in our study was comparable to the above study. Table 5 shows subjective assessment of intubation in both the groups on the basis of Intubation Difficulty Score.…”
Section: Discussionsupporting
confidence: 90%
“…While comparing the Cormack and Lehane grading in both the groups, it was found that grade 1 8,9,14 We did the study with cervical in-line stabilisation and found the same result. None of the patients had Grade-1 glottic visualisation in Macintosh group, the reason may be explained due to poor laryngoscopic view of glottis in cervical in-line position.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Singh showed an 88% effectiveness of EVO2 intubation performed in 28.6 s [18]. Saxena et al, in a study among 140 surgical patients, observed that anaesthesiologists needed an average of 34.1 s to perform intubation using EVO2, which was a statistically significantly longer time than they required for direct laryngoscopy intubation (22.4 s) [19]. Similarly, a longer intubation time using EVO2 as compared with MAC (33.06 ± 5.6 vs. 23.11 ± 5.7 s, respectively) was noted by Timanaykar et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study all the intubation were successfully performed in both the groups, which was in accordance with observation of various other studies. (21)(22)(23)(24) However, some studies (25,26) show higher success rate with videolaryngoscope as compared to Macintosh laryngoscope. The lower success rate in Macintosh group might be due to inclusion of Mallampati grade 1 and 2 patients.…”
Section: Demographic Datamentioning
confidence: 99%